Novel and recurrent XYLT1 mutations in two Turkish families with Desbuquois dysplasia, type 2 - ELÇİOĞLU, HURİYE NURSEL (NATURE PUBLISHING GROUP, 2017)
Desbuquois dysplasia (DBQD) is an autosomal recessive skeletal disorder characterized by growth retardation, joint laxity, short extremities, and progressive scoliosis. DBQD is classified into two types based on the presence (DBQD1) or absence (DBQD2) of characteristic hand abnormalities. CANT1 mutations have been reported in both DBQD1 and DBQD2. Recently, mutations in the gene encoding xylosyltransferase 1 (XYLT1) were identified in several families with DBQD2. In this study, we performed whole-exome sequencing in two Turkish families with DBQD2. We found a novel and a recurrent XYLT1 mutation in each family. The patients were homozygous for the mutations. Our results further support that XYLT1 is responsible for a major subset of DBQD2.
Keywords: DIASTROPHIC DYSPLASIA; HOMOZYGOUS MUTATION; SKELETAL; FEATURES; ENCODES; PATIENT